A Critical Reflection to Improve Diversity, Equity, and Inclusion in the Classroom - Amy M. Anderson (Journal of Scholarly Engagement)
The purpose of this reflective practice was to critically examine an unexpected revelation that I did not have the skills needed to effectively teach in a diverse classroom. As a communication studies instructor at the community college and university level, I teach students from various backgrounds. Yet, I lacked knowledge about the elements of these students’ identities that impact their learning, such as their differing abilities, genders, cultures, and socioeconomic statuses. After an intensive year of professional development on diversity, equity, and inclusion, I finally had the knowledge to better serve my students. Next, I reflected on how I could use these insights to improve my course curriculum, relationship with students, and teaching practices. Furthermore, I developed a checklist for educators to use as a self-reflection tool to better inform their teaching practices in a diverse classroom.